Letter to Jane Tolmach from Rita Dobson - Rita Dobson:::::: (1976)
In a May 5, 1976 letter, the California Federation of Business and Professional Women's Clubs informed Jane Tolmach that it had unanimously voted to endorse and support her candidacy for the 36th Assembly District. The organization enclosed a $1,000 contribution to assist her campaign. Rita Dobson, Chair of Political Promotion and Political Education, expressed best wishes for the primary and offered further assistance if needed. She also noted a leadership transition within the committee. The letter emphasized the group's "Women Helping Women" plan to elect qualified women to public office.